The genotypic characterization of Streptococcus pluranimalium from aborted bovine fetuses in British Columbia, Canada - Yee, Marcus; Trimble, Michael J.; Ghosh, Kazal; Hughes, Giselle; Knowles, Daniel; Duan, Jun; Raverty, Stephen; McGregor, Glenna; Hsiao, William W. L. (Frontiers in Microbiology, 2025)
IntroductionBovine abortions result in significant economic losses to dairy producers, and bacteria are among the most common causes of these abortions. In 2021, Streptococcus pluranimalium was isolated from a dairy abortion case for the first time in British Columbia (BC), Canada. This bacterium has previously been recovered from the reproductive tracts of dairy cattle and various other species, including humans.MethodsBetween 2021 and 2023, S. pluranimalium was isolated from the placenta, fetal lung, and/or fetal abomasal contents of 10 aborted dairy fetuses submitted for routine abortion diagnostics. This study was conducted to better characterize the genotype of these 10 isolates. The histopathology of the bovine abortions was examined, and the BC strains were sequenced using Nanopore technology and underwent bioinformatic analysis.ResultsThe BC strains had an average genome size of 2,313,582 base pairs and an average GC content of 38.59%. Based on whole genome phylogeny, the BC strains were clustered together and distinctly separated from other publicly available strains of this species from different regions and isolation sources. Through Clusters of Orthologous Groups analysis, the BC strains contained a larger proportion of genes associated with the mobilome. Additionally, although we identified only a few antibiotic resistance genes or virulence factors (VFs) in these strains, several of these genes were located within prophage sequences.DiscussionAlthough the clinical and pathological significance of these bacteria in most abortion cases remains unclear, our findings underscore the importance of continued surveillance and research into uncommon pathogens to better understand their biology and potential impact on human and animal health.